Autism in Peru: An outlook from autism research and work team - Reaño Carranza, Ernesto (2022)
EITA was founded in 2009 by Mg. Ernesto Reaño in order to provide support services to the autistic community, caregivers and family members, and working towards the implementation of adjustments and supports in the various social contexts seeking accessibility for this population. EITA is pioneer in Peru working on the neurodiversity paradigm, the implementation of adequate services for each autistic person, respecting their development age, sexual orientation, gender identity,  cultural identity, etc. without any discrimination. In this sense, it is part of the constant support for the recognition of the human rights of the autistic person and the neurodiversity movement.